2001
DOI: 10.1163/22941932-90000264
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Function of Intervessel Pits Through a Growth Ring Boundary of Machilus Thunbergii

Abstract: Vessels in some species are connected by intervessel pits on the tangential walls of radial multiples, which may allow the radial flow of sap. This network was investigated in Machilus thunbergii Sieb. et Zucc., a diffuse-porous wood with radial multiples extending through growth ring boundaries. Air permeability measurements suggest radial flow paths exist through a growth ring boundary. Flow paths were pressurestained with reduced basic fuchsin solution. Observations of serial cross sections confirmed the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…Each vessel makes sequential contacts along its course with a number of other vessels (Burggraaf 1972;Fujii et al 2001;Tyree and Zimmermann 2002;Kitin et al 2004). Numerous pits are present at these sites of contact, allowing lateral flow of water between vessels in both radial and tangential directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each vessel makes sequential contacts along its course with a number of other vessels (Burggraaf 1972;Fujii et al 2001;Tyree and Zimmermann 2002;Kitin et al 2004). Numerous pits are present at these sites of contact, allowing lateral flow of water between vessels in both radial and tangential directions.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have pointed out the importance of lateral flow in plants; Taneda and Tateno (2007) showed that radial flow within the internode contributes significantly to the effective water supply to the leaf. Fujii et al (2001) and Kitin et al (2009) demonstrated that lateral transport has potentially important implications in the growth of cambium and differentiating xylem elements. Moreover, the large potential for lateral flow provides a mechanism for rapid and sustainable water movement around blocked vessels, because water can easily bypass vessel occlusions by lateral movement to other functioning vessels (Tyree and Ewers 1991;Tyree et al 1994;Tyree and Zimmermann 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the frequency and properties of the pits will affect not only the mode of air seeding, but also the xylem's hydraulic conductance, implying that variation in the bordered pit structure could reflect the adaptive balance between hydraulic efficiency and hydraulic safety at different locations within a plant. The sizes of the openings between the margo strands are likely to be the hydraulic bottleneck controlling water flow between tracheids because water must move laterally through the membrane (Fujii et al, 2001), a requirement that explains the low radial xylem conductivity (Kitin et al, 2004;Domec et al, 2006). Therefore, in addition to conduit diameter, the size and frequency of the margo pores as well as overall pit frequency should be important anatomical determinants of tracheid hydraulic conductivity (Stone, 1939;McCully and Canny, 1988).…”
mentioning
confidence: 99%
“…During the evolution of land plants, these elements developed features that allow the efficient and reliable transport of water (Bailey, 1953;Carlquist, 1975Carlquist, , 1988Baas, 1976Baas, , 1982Tyree and Zimmerman, 2002;Sperry, 2003). Studies of the structure of vessels and their three-dimensional (3-D) networks could lead to a better understanding of the pathways of the ascent and distribution of water in the plant body, as well as of plant strategies for adaptation of xylem structure to various environments, in particular, the way in which water transport is assured in cases of injury or embolism (Utsumi et al, 1999; and the way in which xylem structure is optimized with respect to its hydraulic and biomechanical properties (Gartner, 1991a, b;Niklas, 1992;Fujii et al, 2001;Woodrum et al, 2003).…”
mentioning
confidence: 99%